2013
DOI: 10.1016/j.jcrc.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative plasma melatonin concentration in postoperative critically ill patients: Its association with delirium

Abstract: Purpose: Delirium is a common complication in postoperative critically ill patients. Although abnormal melatonin metabolism is thought to be one of the mechanisms of delirium, there have been few studies in which the association between alteration of perioperative plasma melatonin concentration and postoperative delirium was assessed. Materials:We conducted a prospective observational study to assess the association of perioperative alteration of plasma melatonin concentration with delirium in 40 postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 24 publications
2
33
0
1
Order By: Relevance
“…20) The risk of delirium in preoperative patients has been reported to increase when the melatonin concentration is low and to decrease with prophylactic oral administration of ramelteon. 21,22) The fact that no signal was seen for ramelteon in the present study also suggested that ramelteon is not involved in the onset of delirium.…”
Section: Discussionsupporting
confidence: 44%
“…20) The risk of delirium in preoperative patients has been reported to increase when the melatonin concentration is low and to decrease with prophylactic oral administration of ramelteon. 21,22) The fact that no signal was seen for ramelteon in the present study also suggested that ramelteon is not involved in the onset of delirium.…”
Section: Discussionsupporting
confidence: 44%
“…Recent studies measured the postoperative plasma concentration of melatonin and the urinary excretion of 6-sulfatoxymelatonin (6-Sheng Chen and LiGen Shi contributed equally to this work. SMT) as the chief metabolite of melatonin, where it was found that plasma melatonin was significantly lower in elderly patients with delirium [14][15][16], and urinary 6-SMT was higher in hypoactive delirium and lower in hyperactive delirium [17]. Several studies have also shown that elderly individuals tend to have an age-related suppression in the amplitude of nocturnal peak level of melatonin, which puts them at a higher risk of developing delirium [2,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…According to the association between delirium and irregular patterns of melatonin secretion, which has been described by several studies, irregular melatonin secretion could be one of the mechanisms of delirium (10,23,30,31,(50)(51)(52) as well as the presence of sleep deprivation in hospitalized delirious patients at the ICU, as it has been indicated that melatonin and its agonists could be an effective supplement for prevention and management of delirium (38,53,54). Furthermore, several studies have reported the marked improvement of delirium in delirious patients without side effects due to the use of melatonin and ramelteon (6,45,46).…”
Section: Discussionmentioning
confidence: 99%